Durability study on glass fiber reinforced polymer soil nail via accelerated aging test and long‐term field test. Issue 12 (22nd December 2015) - Chen, Zhi; Zheng, Lifei; Jin, Qingping; Li, Xiaoqing
Abstract : Replacing steel reinforcements with glass fiber reinforced polymer (GFRP) bars has emerged as one of the most promising solutions to the problem of corrosion in geotechnical engineering. Accelerated aging and field tests were conducted to investigate the durability of GFRP bars that were used as soil nails in slope reinforcement. Two types of E‐glass/(vinylester and unsaturated polyester) were immersed in alkaline and saline solutions for 60 d, 180 d and 360 d. Mechanical and physical experiments were carried out to obtain the tensile strength and identify the reasons for damage and strength reduction. A pullout test was carried out after the GFRP soil nails were embedded in a slope for three years. The accelerated aging test results showed that alkaline conditions had a larger influence on the degradation of GFRP bars than did saline solutions and that strength reduction generally occurred at an earlier stage for the alkaline conditions than for the saline solution. The corrosion resistance of an unsaturated polyester bar is much lower than that of the vinylester bar, and the bar diameter has a certain impact. From the field test results, it can be seen that the GFRP soil nails are durable and perform well at the task of supporting a slope. The technology for sensing fiber Bragg gratings (FBG) is very convenient for monitoring soil nails and is suitable for long‐term observation. POLYM. COMPOS., 38:2863–2873, 2017. © 2015 Society of Plastics Engineers